2021
DOI: 10.3389/fcell.2021.641763
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Extracellular Vesicles Increase Col8a1 Secretion and Vascular Stiffness in Intimal Injury

Abstract: The arterial mechanical microenvironment, including stiffness, is a crucial pathophysiological feature of vascular remodeling, such as neointimal hyperplasia after carotid endarterectomy and balloon dilatation surgeries. In this study, we examined changes in neointimal stiffness in a Sprague-Dawley rat carotid artery intimal injury model and revealed that extracellular matrix (ECM) secretion and vascular stiffness were increased. Once the endothelial layer is damaged in vivo, activated platelets adhere to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…4 E). Given that miR-92a level is significantly increased in carotid arteries after intima injury 13 , we analyzed RNA-seq data (GSE164050) from carotid arteries. Consistent with our results, marker genes of the contractile phenotype of VSMCs were downregulated, and those of the proliferative phenotype were upregulated in carotid arteries (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 E). Given that miR-92a level is significantly increased in carotid arteries after intima injury 13 , we analyzed RNA-seq data (GSE164050) from carotid arteries. Consistent with our results, marker genes of the contractile phenotype of VSMCs were downregulated, and those of the proliferative phenotype were upregulated in carotid arteries (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Upon vascular damage, activated platelets adhere to the intima, then secrete platelet-derived EVs. These miR-92a-containing EVs, when transported to VSMCs, can induce Col8a1, which augments vascular stiffness 13 . Our results showed that Ang II increased miR-92a level in ECs, which resulted in EC dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 E. We found that the expression of mineralization markers such as BGN, COL11A1 , and COL10A1 were significantly increased [ [30] , [31] , [32] , [33] ]. Similarly, the expression of vascular and neurological differentiation markers such as COL8A2 and ANKRD1 also increased to a certain extent [ 34 , 35 ]. Furthermore, these results demonstrated that the odontogenesis of hDPSCs was promoted by TDM induction.…”
Section: Resultsmentioning
confidence: 99%
“…Astrocytes are known to secrete ECM proteins that provide a substrate for endothelial tip cell migration and the formation of superficial retinal vasculature [12,14,63,15]. Defect or changes in ECM molecular composition could alter vascular growth and vascular matrix integrity [64,14,65]. As prior report indicate a role for C3a-C3aR axis in regulating proteases mediated ECM remodeling [66], enrichment of ECM related genes in C3 and C3aR deficient retinas suggest a possible defect in remodeling of ECM components involved in angiogenesis [64,14,65].…”
Section: Discussionmentioning
confidence: 99%